Impact of Sleep Quality, Workload, Job stress, and Coping Strategies on Work Fatigue among Nurses at Hermina Hospital Manado - Siti Adrianti; Theresia M. D. Kaunang; Greta J.P. Wahongan; Harsali Fransiscus Lampus; Dina Victoria Rombot (LPPM Universitas Harapan Bangsa, 2024)
Work fatigue in nurses affects patient care, including patient safety, the risk of patient falls, and medical errors, and decreases organizational performance. This study evaluates the relationship between sleep quality, workload, job stress, and coping strategies with work fatigue among nurses at Hermina Manado Hospital. The approach utilized involves observational analysis using a cross-sectional method involving a sample of 63 nurses, using questionnaires, Spearman correlation analysis and logistic regression. The results show that most respondents experienced moderate levels of work fatigue (69.8%), poor sleep quality (61.9%), heavy workload (57.1%), moderate job stress (63.5%), and use of emotion-based coping strategies (85.7%). Spearman correlation showed a positive relationship between sleep quality (r = 0.444; p = 0.000), workload (r = 0.429; p = 0.000), job stress (r = 0.507; p = 0.000), coping strategies (r = 0.268; p = 0.034) and work fatigue. Multivariate analysis yielded (Exp(B) 14.756; p = 0.019) for job stress. It can be inferred that there is a relationship between sleep quality, workload, job stress, and coping strategies with work fatigue in nurses, with the most dominant factor being job stress.